Optimizing support patch geometries in adhesively bonded single lap joints - Çalik, Ahmet (Strojniški vestnik, 2025)
In recent years, the preference for adhesive bonding over traditional methods like bolted or riveted connections has garnered the attention of researchers. This study employs finite element analysis to optimize the geometry and placement of support patches in adhesively bonded single lap joints, significantly reducing stress concentrations and enhancing joint strength. Initially, a comprehensive finite element analysis was conducted to numerically evaluate the influence of different support patch parameters and their positions on the strength of single lap joints (SLJs). To validate the finite element analyses (FEA), comparisons were made with existing studies in the literature and analytical solutions. The numerical results in this study reveal that the dimensions and placement of the support patch can potentially reduce the load and stress distribution in different regions of the adhesive joint, which could increase its strength.
Keywords: adhesive bonding; finite element analysis; geometrija podpornih ojačitev; lepljeni spoji; metoda končnih elementov; optimizacija napetosti; stress optimization; support patch geometry